First prenatal diagnosis of a 'pure' 9q34.3 deletion (Kleefstra syndrome): A case report and literature review. Issue 3 (21st November 2017) - Guterman, Sarah; Hervé, Bérénice; Rivière, Julie; Fauvert, Delphine; Clement, Patrice; Vialard, François
Abstract: Kleefstra syndrome (KS) is characterized by developmental delay, intellectual disability, hypotonia and distinct facial features. Additional clinical features include congenital heart defects, cerebral abnormalities, urogenital defects and weight gain. The syndrome is caused by a microdeletion in chromosomal region 9q34.3 (in 85% of cases) or by a mutation in the EHMT1 gene coding for euchromatin histone methyltransferase 1. The prenatal phenotype has not yet been characterized. Herein, we sought to define this phenotype on the basis of a new case report and literature review.